Lubang Hitam Akhir dari Ornamen Jagad Raya - Yunus, Firdaus M. (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
This article analyzed formulation and the end of the world. The matter of the world in the direction of essence dosen't have explicit significance, therefore the only assignment of the philosopher and the scientist is to investigate how evertything be descended from, expand, evolve, or become extinct.The exsistence of the world is apparently unimaginable by human being because the inside of the world have various inanimate object. The object which may dissolve it, among other of the object is the black hole, because the black hole is make up the space and time sphere. There is no object or radiance which able slip away because sturdy gravity. The exsistence of the black hole more explicit with something found celestial on November 18, 2002 with rush by Bima Sakti Galaxy and drawn about the old stars.